Preliminary investigation to review if a glycomacropeptide compared to l-amino acid protein substitute alters the pre-and postprandial amino acid profile in children with phenylketonuria - Daly, Anne (2020)
In Phenylketonuria (PKU), the peptide structure of the protein substitute (PS), casein glycomacropeptide (CGMP), is supplemented with amino acids (CGMP-AA). CGMP may slow the rate of amino acid (AA) absorption compared with traditional phenylalanine-free amino acids (Phe-free AA), which may improve nitrogen utilization, decrease urea production, and alter insulin response. Aim: In children with PKU, to compare pre and postprandial AA concentrations when taking one of three PS’s: Phe-free AA, CGMP-AA 1 or 2. Methods: 43 children (24 boys, 19 girls), median age 9 years (range 5–16 years) were studied; 11 took CGMP-AA1, 18 CGMP-AA2, and 14 Phe-free AA. Early morning fasting pre and 2 h postprandial blood samples were collected for quantitative AA on one occasion. A breakfast with allocated 20 g protein equivalent from PS was given post fasting blood sample. Results: There was a significant increase in postprandial AA for all individual AAs with all three PS. Postprandial AA histidine (p < 0.001), leucine (p < 0.001), and tyrosine (p < 0.001) were higher in CGMP-AA2 than CGMP-AA1, and leucine (p < 0.001), threonine (p < 0.001), and tyrosine (p = 0.003) higher in GCMP-AA2 than Phe-free AA. This was reflective of the AA composition of the three different PS’s. Conclusions: In PKU, the AA composition of CGMP-AA influences 2 h postprandial AA composition, suggesting that a PS derived from CGMP-AA may be absorbed similarly to Phe-free AA, but this requires further investigation.